Thermal sensation, rate of temperature change, and the heat dissipation design for tablet computers. (July 2017) - Zhang, Han; Hedge, Alan; Cosley, Daniel
Abstract: Past research has shown that the rate of change of skin surface temperature can affect thermal sensation. This study investigated users' thermal responses to a tablet heating surface with different heat pads and different temperature change rates. The test conditions included: A. keeping the surface at a constant 42 °C, B. increasing the surface temperature from 38 °C to 42 °C at a rate of 0.02 °C/s in progressive intervals, C. increasing the temperature at 0.15 °C/s in progressive intervals, and D. Heating two left and right side pads alternately from 38 °C to 42 °C at 0.15 °C/s in progressive intervals. Overall results showed the lowest temperature change rate of 0.02 °C/s was most preferred in terms of thermal comfort. The findings suggest a potential to improve user thermal experience by dissipating tablet computer heat at a lower temperature change rate, or by alternating the dissipation areas. Highlights: A tablet prototype was built, which can control the rate of temperature change and heated areas. A slow temperature change rate can lead to a higher comfort than a faster rate. Slower rate temperature change may improve heat dissipation for future computers of small form factors.